2020
DOI: 10.1007/s12053-020-09888-y
|View full text |Cite
|
Sign up to set email alerts
|

Fostering investment in resource efficiency actions: the case of European SMEs

Abstract: The present paper analyses the factors associated with intensity in resource efficiency practices of European SMEs, considering four categories of firms according to their level of investment (very low, low, medium and high). Based on the stakeholder theory, we estimate a generalised ordinal logistic model which allows us to analyse the relationship between internal and external pressures, resources and capabilities and different categories of investments in resource efficiency. Results confirm that environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 71 publications
(122 reference statements)
2
17
0
Order By: Relevance
“…According to Ghisetti and Rennings [4], eco-innovation is classified as follows: (1) energy efficient innovation, that is, an innovation that reduces energy and/or material use; (2) environmental innovation, that is, an innovation that reduces negative environmental impacts, such as air, water pollution, and harmful materials. However, both types of eco-innovation (i.e., those that reduce pollution or those that reduce energy) face the "double externality problem" typical for eco-innovation [34,35], and reduce the negative environmental impact. Meanwhile, Arranz et al [36] suggested measuring eco-innovation activity of the firm by considering the following criteria: (1) less energy per production; (2) lower environmental impact; (3) improvement in health and safety; (4) compliance with regulatory requirements.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…According to Ghisetti and Rennings [4], eco-innovation is classified as follows: (1) energy efficient innovation, that is, an innovation that reduces energy and/or material use; (2) environmental innovation, that is, an innovation that reduces negative environmental impacts, such as air, water pollution, and harmful materials. However, both types of eco-innovation (i.e., those that reduce pollution or those that reduce energy) face the "double externality problem" typical for eco-innovation [34,35], and reduce the negative environmental impact. Meanwhile, Arranz et al [36] suggested measuring eco-innovation activity of the firm by considering the following criteria: (1) less energy per production; (2) lower environmental impact; (3) improvement in health and safety; (4) compliance with regulatory requirements.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Previous experience [25,64] Technological capabilities [34,70] Green capabilities [34,69] Innovation capabilities [64] Knowledge development [25] Organizational innovation [33,67] Financial resources [34] Investment in tangible assets [67] Meso Market dynamics Competitive pressure [5] Customer and provider pressure [34,38,39…”
Section: Resources and Capabilitiesmentioning
confidence: 99%
See 3 more Smart Citations